The Stenopsyche simplex Species Group from China with descriptions of three new species (Trichoptera: Stenopsychidae) - Xu, Ji-Hua; Wang, Bei-Xin; Sun, Chang-Hai (Zootaxa, 2014)
The Chinese Stenopsyche simplex Group is revised for the first time since Weaver’s (1987) revision. The group includes 14 described species and 3 new species. Two diagnostic subgroups were recognized by Schmid (1959). The first subgroup of Chinese species includes S. anaximander Malicky 2011, S. brevata Tian & Zheng 1989, S. chinensis Hwang 1957, S. dentata Navás 1930, S. splendida Martynov 1935, S. dubia Schmid 1965, S. rotundata Schmid 1965, S. simplex Schmid 1959, and S. tienmushanensis Hwang 1957; of these, S. dentata is assigned to this first subgroup for the first time. The second diagnostic subgroup includes S. denticulata Ulmer 1926, S. longispina Ulmer 1926, S. stoetzneri Döhler 1929, S. uniformis Schmid 1965 and S. formosana Kobayashi, 1987. The species newly described here include Stenopsyche ningshanensis sp. nov., from Shaan-xi Province, belonging to the first subgroup, and Stenopsyche acanthoclada sp. nov. and Stenopsyche jinxiuensis sp. nov., both from Guang-xi Province and belonging to the second subgroup. Distribution maps of the two diagnostic subgroups of Chinese species and illustrations of male genitalia of the three new species are provided along with collection data for additional specimens for the previously described species.